Phase-out of 'coal to power' in an ETS - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate the displacement effects of phase-out-of-coal policies in a stylized model of electricity generation and CO2 regulation, in which a group of countries operates an emissions trading scheme (ETS). Electricity markets are either international or national and the emissions cap remains either unchanged or is tightened. With constant emissions cap and trade in electricity, some emissions as well as some coal-based electricity `leak' into other countries and the aggregate welfare of the group of countries declines, if a country unilaterally phases out coal. With constant emissions cap and no trade in electricity, the unilaterally phasing-out country is worse off and the other countries are better off. Following a suggestion in a recently revised EU ETS Directive, we then combine a country's phase-out policy with canceling the permits it formerly used to generate electricity from coal. When electricity is traded, that combined policy prevents the leakage of emissions and coal-based electricity and shifts a share of the welfare costs to other countries. Without trade in electricity, the other countries generate less coal-based electricity and all countries' consumption welfare decreases, but all countries benefit from reduced climate damage. Finally, we offer an empirical calibration of our model to the European Union.
Keywords: H22; Q37; Q48; 330; phase-out; gas; electricity; leakage; ETS